2017
DOI: 10.1097/md.0000000000006409
|View full text |Cite
|
Sign up to set email alerts
|

Increased HPV L1 gene methylation and multiple infection status lead to the difference of cervical epithelial cell lesion in different ethnic women of Xinjiang, China

Abstract: Human papillomavirus (HPV) L1 gene methylation deeply involved in the progression and heterogeneity of cervical cell epithelial lesions. The DNA ploidy also represented the early lesions of cervical cell, and it was associated with different HPV infection status in different ethnic women. So, the research was to explore whether it was possible that HPV L1 gene methylation and HPV infection status as the risk factors to lead to the differences of cervical epithelial cells’ lesions in different ethnics women.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…One study suggested that routine cancer screening in the population with CKD is a relatively inefficient allocation of financial resources, because the net gain in life expectancy from a typical cancer screening program was calculated to be 5 days or less and the gain of survival could be obtained via a reduction of 0.02% or less in the baseline CKD-related mortality rate. [ 42 , 43 ] In the current study, we did not find the increased risk of GC in the younger group (Table 4 ). By contrast, we found that the GC risk was similar in these younger women (< 40 years), regardless of women with or without CKD.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…One study suggested that routine cancer screening in the population with CKD is a relatively inefficient allocation of financial resources, because the net gain in life expectancy from a typical cancer screening program was calculated to be 5 days or less and the gain of survival could be obtained via a reduction of 0.02% or less in the baseline CKD-related mortality rate. [ 42 , 43 ] In the current study, we did not find the increased risk of GC in the younger group (Table 4 ). By contrast, we found that the GC risk was similar in these younger women (< 40 years), regardless of women with or without CKD.…”
Section: Discussioncontrasting
confidence: 60%
“…In addition, these CKD women subsequently may have a prolonged latency of HPV infection or persistent HPV infection, which is a key factor for the development of cervical pre-cancer lesions and cancers in women. [ 40 42 ] Furthermore, some studies showed that the CKD women were substantially less likely to undergo cervical cancer screening compared with women without CKD. [ 21 , 22 ] Both provided a good reason to explain the finding of an increased risk of cervical cancer in the CKD women with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer was one of the most common malignant tumors in China, in which its prevalence rate was 7th in all cancers and its mortality was 8th in all female cancers [1]. HPV infection is known as the main cause of cervical cancer; most of HPV infection could be cleaned by the host immune responses, but some persistent HPV infection would lead to the cytopathy of cervical cancer cells [2][3][4]. The previous studies found that the HPV persistent infection consisted of two phases: in the first phase of viral replication, HPV firstly infected basal cells of the cervix, bare virus DNA was the free state in the host cell nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…One of the epigenetic mechanisms that are increasingly studied is HPV genes' methylation. At present, a consistent correlation of increased methylation of capsid viral genes with histology severity is referred by the researchers 7, 9, 11, 19, 20. On the other hand, studies on methylation status of the UTR , E6 and E7 regions reveal heterogeneous and rather inconclusive results 21-25.…”
Section: Discussionmentioning
confidence: 67%